Evaluation of Child’s Right Portrayal in Select Nollywood Films - Majumder, Rajib; Onyejelem, Timothy Ekeledirichukwu; Nwokeocha, Ifeanyi Martins Nwokeocha (International Journal of Applied and Scientific Research, 2024)
This study examines the role of Nollywood films in promoting child rights in Nigeria. Using Development Media and Social Representation Theories, the study analyzed five locally produced movies and 663 respondents. The findings revealed that Nigerian films depict various issues of child rights, including neglect, child labor, emotional abuse, child battering, sexual abuse, gender discrimination, child kidnapping, child trafficking, and moral abuse. The study concluded that Nigerian movies provide a country perspective for deepening moral and social consciousness and advancing attitudinal change in child rights. The authors recommend that filmmakers continue producing films that address child rights issues to further advance justice against children.